(untitled) (Bangladesh Journal of Microbiology, 2023)
More than 4.5 million people nationwide have experienced diarrhea in the country’s most recent outbreak, which began on March, 2022. About 70% to 80% of patients (of whom 23% had severe diarrhea or cholera) were hospitalized. Several factors were associated with the risk for diarrhea include; unhygienic and unsafe environment, age, low educational status of mothers, employment status, family size, income, poor handling of drinking water at household level, place of residence, unhygienic disposal method of feces and wastes, lack of personal hygiene and lack of access to sanitation facilities. In addition, etiology, influence of climate and geographical location, diagnosis capability, hygiene education, and infrastructure are strongly linked to the high frequency of diarrhea and play a crucial role in efficiently managing diarrhea. We observed that a significant proportion of people with diarrheal illnesses continue to seek care from unqualified healthcare practitioners since inaccessibility from professional healthcare providers. Dissemination of information on health education, increasing the supply of skilled healthcare providers, and low-cost and quality healthcare services may encourage more people to seek care from professional healthcare providers, thus may help reducing mortality in the country. In conclusion, the policy mechanisms to increase systems’ resilience, some engineering approaches include source, treatment, distribution, and point-of-use control measures could be implemented to manage microorganism proliferation in drinking water. Bangladesh J Microbiol, Volume 39, Number 1, June 2022, pp 39-45